Satellite Yield Mapping in Kenya and Nepal - Campolo, Jake (2019)
Jake Campolo WEBINAR Using Satellite Imagery for Early Warning of Productivity Constraints Organized by the Food Security Portal (FSP) OCT 31, 2019 - 11:00 AM TO 12:30 PM EDT